INCORPORATING CULTURAL FACTORS IN EFL CONTEXT - Aam Alamsyah; Mutaat Mutaat; Radik Darmawan (English Review: Journal of English Education, 2019)
This study highlighted the issue of the incorporation of English cultures, cultural preference and diversity in relation to the students’ English program. The need to analyze the students’ perception is imperative since the students are considered as one of the most important factors in determining the success or failure of their own learning process.  The respondents recruited for the present study were 80 part-time college students of different departments (i.e., Literature, Informatics, and Accounting). The use of mixed method aimed to elicit more elaborate data on the students’ perceptions toward the above issues. The instruments used in the present study were questionnaires and semi-structured interview. During the data collection, the questionnaire, and interview were administered within the same day. The results indicated that the students’ perception toward the incorporation of English culture was ambivalent.  Of the 80 participants, there were only 48 students who voiced to agree and to strongly agree with the exposure; while the rest of the participants did not seem to agree. It was also found that most of the students preferred to learn Asian cultures instead of western ones. The most noticeable determinants affecting their preference were mainly the popularity of Asian cultures exposed on various media as well as their jobs which mostly involved Asian employers (Japanese, Korean, etc.). They were also found to appreciate the exposure conducted by the teacher as one of the relevant activity when learning foreign language. English grammar and vocabulary are skills to prioritize when speaking with Asians, and they did not find pronunciation important to support communication among them.